Comparative Effectiveness of Learning Starts with a Question and Question Students Have Strategies on Junior Secondary Students’ Mathematics Achievement - M, Nur Akbar; Moncobalang, Abnaul Amir; Norma, Norma (jurnal matematika, 2025)
Purpose of the study: This study examined the comparative effectiveness of two question-based active learning strategies, namely Learning Starts with a Question and Question Students Have, on junior secondary students’ mathematics achievement. Methodology: A quasi-experimental non-equivalent control group design was employed involving two Grade Eight classes. One class was taught using the Learning Starts with a Question strategy and the other using the Question Students Have strategy. Mathematics achievement was measured using validated essay tests administered as pretest and posttest. Data were analysed using descriptive statistics and independent samples t-test after normality and homogeneity assumptions were met. Main Findings: Both strategies improved students’ mathematics achievement. The class taught using the Learning Starts with a Question strategy obtained a higher posttest mean score of 84.16 compared to the class taught using the Question Students Have strategy with a mean score of 79.72. Independent samples t-test indicated a significant difference between the two classes with a probability value of 0.009. The increase in scores from pretest to posttest was also higher in the Learning Starts with a Question class, indicating greater improvement in mathematics learning outcomes. Novelty/Originality of this study: The Learning Starts with a Question strategy is more effective than the Question Students Have strategy in improving junior secondary students’ mathematics achievement. Initiating mathematics instruction with student-generated questions enhances cognitive readiness and supports conceptual understanding.